A node division location detection scheme for chain‐type wireless sensor networks. Issue 1 (26th July 2014) - Chen, Guangzhu; Bao, Jiusheng; Zhang, Lei
Abstract: As a special type of wireless sensor network, the chain‐type wireless sensor networks can be used to monitor narrow and long regions, such as roads, underground mine tunnels, rivers, and bridges. In this study, a perpendicular bisector division (PB) method was first presented, in which the location may be divided into more location sub‐areas by a perpendicular bisector of each of two location nodes. Compared with the triangulation division method in Approximate Point‐in‐Triangulation Test (APIT), the computable complexity of PB is lower, and the number of division areas is larger. Furthermore, in order to locate targets under rare location nodes, a virtual location node‐perpendicular bisector division (VPB) was presented by a virtual location node based on the geographic shape of the monitored area. Virtual location nodes increase the density of location nodes, which can improve the accuracy of the location in the location algorithm. Second, two range‐free location algorithms were proposed: the location algorithm based on PB (LAPB) and the location algorithm based on VPB (LAVPB). In the end, the location errors performance of APIT, LAPB, and LAVPB for locating miners in an underground mine tunnel was tested. The results show that LAPB and LAVPB have higher location accuracy and are more robust than APIT. LAVPB is more suitable for locating targets in harsh environments. Copyright © 2014 John Wiley & Sons, Ltd. Abstract : A virtual location node‐perpendicular bisector division method (VPB division) in WSN can divide the location region into a number of sub‐areas by perpendicular bisectors of every two sensing nodes, and increase the node density in the network.